A novel β-xylosidase from Anoxybacillus sp. 3M towards an improved agro-industrial residues saccharification - Marcolongo, L. (2019)
ABSTRACT: An intracellular β-xylosidase (AbXyl), fromthe thermoalkaline Anoxybacillus sp. 3M,was purified and characterized. The homodimeric enzyme (140 kDa) was optimally active at 65 °C and pH 5.5, exhibited half life of 10 h at 60 °C, 78 and 88% residual activity after 24 h, at pH 4.5 and 8.0, respectively. Fe2+, Cu2+, Al3+, Ag+ and Hg2+inhibited the enzyme; the activity was moderately stimulated by SDS and not influenced by β-mercaptoethanol. In the presence of p-nitrophenyl-β-D-xylopyranoside, AbXyl exhibited Km of 0.19 mM, Kcat of 453.29 s−1, KcatKm−1 of 2322 s−1mMandwas moderately influenced by xylose (Ki 21.25mM). The enzyme hydrolyzed xylo-oligomers into xylose and catalyzed transxylosilation reactions also in presence of alcohols as acceptors, producing xylo-oligosaccharides and alkyl-xylosides. Finally AbXyl was applied towards a statistically optimized process of brewery's spent grain bioconversion, highlighting the important role of this biocatalyst in reaching high yields of fermentable sugars.